Grounding‐Zone Flow Variability of Priestley Glacier, Antarctica, in a Diurnal Tidal Regime. Issue 20 (11th October 2021) - Drews, R.; Wild, C. T.; Marsh, O. J.; Rack, W.; Ehlers, T. A.; Neckel, N.; Helm, V.
Abstract: Tidal modulation of ice streams and their adjacent ice shelves is a real‐world experiment to understand ice‐dynamic processes. We observe the dynamics of Priestley Glacier, Antarctica, using Terrestrial Radar Interferometry (TRI) and GNSS. Ocean tides are predominantly diurnal but horizontal GNSS displacements also oscillate semi‐diurnally. The oscillations are strongest in the ice shelf and tidal signatures decay near‐linearly in the TRI data over > 10 km upstream of the grounding line. Tidal flexing is observed > 6 km upstream of the grounding line including cm‐scale uplift. Tidal grounding line migration is small and < 40% of the ice thickness. The frequency doubling of horizontal displacements relative to the ocean tides is consistent with variable ice‐shelf buttressing demonstrated with a visco‐elastic Maxwell model. Taken together, this supports previously hypothesized flexural ice softening in the grounding‐zone through tides and offers new observational constraints for the role of ice rheology in ice‐shelf buttressing. Plain Language Summary: Temperatures in Antarctica's interior are below zero, so that ice continuously accumulates through snowfall. This mass gain is balanced by ice transport from the interior toward the coast. There, floating ice shelves form on the ocean and ice is eventually lost through iceberg calving and ocean induced melting. Small changes in any of these processes impact global ocean circulation and mean sea level. The speed of the ice varies with ocean tides. We use a specialized instrument that detects this variability and tidal flexing area‐wide and every few hours. We find that although low‐ and high‐tide only occur once a day in this area, ice flow is largest twice a day. This can be explained because ice softens when it is flexed by the ocean tides so that it can flow episodically faster. This is important because the deformation of ice shelves determines to an extent the stability of the entire ice sheet. Key Points: Terrestrial radar interferometry and GNSS identify dynamic changes at Priestley Glacier, Antarctica, forced by diurnal ocean tides Horizontal displacements vary semi‐diurnally, are strongest in the shelf and decay near‐linearly >10 km upstream of the grounding line Grounding line migration is small and flexural softening in ice‐shelf shear margins can explain the semi‐diurnal ice flow component